106k views
2 votes
Compute the indicated power by using DeMoivre’s theorem:

Compute the indicated power by using DeMoivre’s theorem:-example-1
User LeoNeo
by
5.7k points

1 Answer

7 votes


2+2i=2\sqrt2e^(i\pi/4)


3-3i=3\sqrt2e^(-i\pi/4)


\implies(2+2i)/(3-3i)=\frac23e^(i\pi/2)

By DeMoivre's theorem,


\left((2+2i)/(3-3i)\right)^5=\left(\frac23\right)^5e^(i5\pi/2)=(32)/(243)e^(i\pi/2)=(32i)/(243)

Just to confirm:


(2+2i)/(3-3i)\cdot(3+3i)/(3+3i)=(12i)/(18)=\frac{2i}3\implies\left((2+2i)/(3-3i)\right)^5=(32i)/(243)

User Zenexer
by
6.9k points